The bacterial ATPase SecA functions as a monomer in protein translocation - Or, Eran; Boyd, Dana; Gon, Stéphanie; Beckwith, Jonathan; Rapoport, Tom (The Journal of biological chemistry, 2005)
The ATPase SecA drives the post-translational translocation of proteins through the SecY channel in the bacterial inner membrane. SecA is a dimer that can dissociate into monomers under certain conditions. To address the functional importance of the monomeric state, we generated an Escherichia coli SecA mutant that is almost completely monomeric (>99%), consistent with predictions from the crystal structure of Bacillus subtilis SecA. In vitro, the monomeric derivative retained significant activity in various assays, and in vivo, it sustained 85% of the growth rate of wild type cells and reduced the accumulation of precursor proteins in the cytoplasm. Disulfide cross-linking in intact cells showed that mutant SecA is monomeric and that even its parental dimeric form is dissociated. Our results suggest that SecA functions as a monomer during protein translocation in vivo.